Behold a pale horse : a mystery of ancient Ireland - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels, 2012)
On her trip home from Rome, Sister Fidelma unexpectedly finds herself in Genoa, where she learns of the imminent death of a former mentor who imparts information about a conspiracy that is triggering murders and a vicious war.